Use of Right Ventricular Assist Device Post-Left Ventricular Assist Device Placement - Shannon Parness; Tori E. Hester; Harish Pandyaram; Panagiotis Tasoudis; Aurelie E. Merlo (Hearts)
Right heart failure (RHF) is a common manifestation after left ventricular assist device (LVAD) placement and is associated with a high mortality rate. Historically, RV failure requiring an RVAD at the time of LVAD implantation has been associated with an especially high mortality. However, more recently, some studies have shown reasonable outcomes after LVAD implantation even when an RVAD is required, especially if RV failure is recognized early and treated with RV mechanical support. This article analyzes the current trends and studies investigating the use of RVAD placement post-LVAD implantation with an emphasis on the newest devices and treatment paradigms.